Environmental influences on fruit and vegetable intake: results from a path analytic model. Issue 11 (6th November 2013) - Liese, Angela D; Bell, Bethany A; Barnes, Timothy L; Colabianchi, Natalie; Hibbert, James D; Blake, Christine E; Freedman, Darcy A
Abstract: Objective: Fruit and vegetable (F&V) intake is influenced by behavioural and environmental factors, but these have rarely been assessed simultaneously. We aimed to quantify the relative influence of supermarket availability, perceptions of the food environment and shopping behaviour on F&V intake. Design: A cross-sectional study. Setting: Eight counties in South Carolina, USA, with verified locations of all supermarkets. Subjects: A telephone survey of 831 household food shoppers ascertained F&V intake with a seventeen-item screener, primary food store location, shopping frequency and perceptions of healthy food availability, and supermarket availability was calculated with a geographic information system. Path analysis was conducted. We report standardized beta coefficients on paths significant at the 0·05 level. Results: Frequency of grocery shopping at primary food store ( β = 0·11) was the only factor exerting an independent, statistically significant direct effect on F&V intake. Supermarket availability was significantly associated with distance to utilized food store ( β = −0·24) and shopping frequency ( β = 0·10). Increased supermarket availability was significantly and positively related to perceived healthy food availability in the neighbourhood ( β = 0·18) and ease of shopping access ( β = 0·09). Collectively considering all model paths linked to perceived availability of healthy foods, this measure was the only other factor to have a significant total effect on F&V intake. Conclusions: While the majority of the literature to date has suggested an independent and important role of supermarket availability for F&V intake, our study found only indirect effects of supermarket availability and suggests that food shopping frequency and perceptions of healthy food availability are two integral components of a network of influences on F&V intake.